Zastosowanie metody kowariancji do określenia ryzyka na rynku nieruchomości komercyjnych - Krawczyk, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2005)
The Value at Risk model allows answering the base question asked by investor. How much money could be lost with given financial resources involved into given project, in fixed time and fixed risk preference The covariance method used to estimate VaR is static model, but analytic manner of computing allows, after essential analysis, to determine value at risk relatively clearly and quickly. Presented attempt of initiating tool to analyzing quantified risk of investment on real estate market, specialized for capital market, gives observations: a) in the situation of significant growth of investments on real estate market, financed mainly by banking institutions, there is necessity to work out risk models for this market segment, allowing to limit excessive losses caused by too optimistic prices and inappropriate calculations of the effectiveness of the investment, b) well known and used risk models for capital market are basics for connection the both market segments - capital and real - and empirical verification, including investing projects, c) VaR model can be used for determining quantified risk of an investing project, characterized by profitability ratio Net Present Value, but received results should be treated with limited confidence.